Evaluating and modifying the PHDI for depression prevention: insights from NHANES 2005–2018 - Tan, Jia-xin; Li, Qing-zhong; Mo, Yuan-xin; Zhou, Hong-ping; Miao, Liu; Ruan, Guo-tian; Deng, Teng; Gong, Yi-zhen (Frontiers in Nutrition, 2025)
BackgroundDepression is a significant focus in mental health research, emerging as a pressing public health concern globally. The Planetary Health Diet Index (PHDI), recently proposed by The Lancet to balance health and environmental sustainability, remains unclear in its role in preventing depression—our study aims to investigate this association and seeks to optimize this dietary index.MethodsA cross-sectional analysis was conducted using 2005–2018 NHANES data from 27,868 participants. Dietary quality was measured using PHDI-US, and depressive symptoms were assessed with the Patient Health Questionnaire-9 (PHQ-9; score ≥10 indicating depressive symptoms). Associations between dietary indices and depressive symptoms were analyzed using multivariable logistic regression and restricted cubic splines. Machine learning identified key PHDI-US components, leading to the recalibration of PHDI-US to create PHDI-Fruits.FindingsExcept for the Dietary Inflammatory Index (DII), the PHDI-US, HEI-2020, AHEI, and MEDI all demonstrated protective effects against depression. However, the benefits of PHDI-US were weaker compared to the other indices, particularly among participants with high adherence. Among the components of PHDI-US, fruits had the most significant impact. After recalibrating the PHDI-Fruits component, its ability to reduce depression incidence improved substantially, surpassing that of the other dietary indices.InterpretationOptimizing the preventive effect of PHDI on depression, the recalibrated PHDI-Fruits significantly enhances its ability to prevent depression, effectively improving the applicability of PHDI in populations affected by depression.